(untitled) (Research, Society and Development, 2022)
This study was carried out with the objective of identifying in the literature how the habits and lifestyles of people who experience chronic illness to fibromyalgia and the repercussions of the pandemic situation by coronavirus are being discussed by health professionals. This is an integrative review of the literature that focuses on the realization of a synthesis of the articles and the combination of them on the theme researched; for the bibliographic survey, the flowchart guided by the (PRISMA) was used, composing the final sample 10 articles. The most relevant themes found in the articles were chronic diseases, dimensions of human care, empowerment of women with fibromyalgia, healthy lifestyle, fibromyalgia related to physical activity, depression and quality of life, Covid-19 and chronic diseases. It is concluded that the adoption of good habits contributes to the reduction of the probability of the disease reaching this group of vulnerable people, with the pandemic of the Covid-19 these habits were changed defiantly, exacerbating emotions and anxieties because of fibromyalgia, causing damage in treatment and family dynamics. In addition to contributing to sedentary lifestyle, increased consumption of ultra processed foods and high caloric value, resulting in damage to people’s health. It is suggested the implementation of public policies that promote acts of accessibility to health, with reception and preventive measures to the entire population.